Digital ulcers in scleroderma patients: A retrospective observational study. (June 2016) - De Cata, A; Inglese, M; Molinaro, F; De Cosmo, S; Rubino, R; Bernal, M; Mazzoccoli, G
Background: The guidelines for digital ulcers (DUs) management in systemic sclerosis (SSc) indicate the use of iloprost to induce wound healing and bosentan to prevent the onset of new DU. The aim of our study was to evaluate whether the combination treatment may surmount the effect of the single drug. Methods: We analyzed data regarding 34 patients with SSc and at least one active DU persisting despite 6 months of iloprost therapy, and treated for other 6 months with a combination therapy, i.e. iloprost plus bosentan. Results: Overall, patients initially presented 69 DUs (58 on the fingers and 11 on the legs). At the end of the study 34 (49.3%) DUs were completely healed (responding, R), 18 (26.1%) started the healing process (partially responding, PR), and 17 (24.6%) did not respond (NR) to therapy. No new DU was recorded and the ulcers localized on the legs did not respond to the combination therapy. Finally, data have been analyzed by dividing the patients in two groups according to the fibrosis level on the finger. In the group with mild fibrosis, 83.4% of DUs resulted with showing complete healing while, in the group with severe fibrosis, only 18% of DUs were healed ( P = 0.024). Conclusion: The treatment with iloprost plus bosentan is effective in determining healing of DUs in SSc patients with mild digital skin fibrosis. Conversely, the severity of skin fibrosis strongly influences the healing process of DUs. The study confirmed the efficacy of bosentan to prevent onset of new DUs.